Room-temperature direct arylation of anilides under external oxidant-free conditions using CO2-Derived Dimethyl Carbonate (DMC) as a 'green' solvent - Sahoo, Manoj K.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Chemistryselect, 2017)
Here, an efficient catalytic protocol for direct C-H bond arylation of anilides under base- and external oxidant-free conditions is reported. This reaction proceeds readily at room temperature using CO2-derived dimethyl carbonate (DMC) as a green solvent under visible-light dual catalysis. Later, application of our strategy for the gram-scale synthesis of Boscalid has been successfully shown. An unprecedented unsymmetrical bis-arylation of anilides is also demonstrated under mild, redox-neutral conditions.